Comparative efficacy and acceptability of treatments for depressive symptoms in cognitive impairment: A systematic review and Bayesian network meta-analysis - Jin, Boru; Xv, Yunting; Zhang, Bixuan; Qiao, Lei; Liu, Huayan (Frontiers in Aging Neuroscience, 2022)
Abstract： Background: Depressive symptoms play an essential role in cognition declining, while the benefit and acceptability of treatments for depressive symptoms in cognitive impairment still remain to be clarified. Objective: To comprehensively evaluate the comparative efficacy and acceptability of treatments for depressive symptoms in cognitive impairment based on the quantitative Bayesian network meta-analysis method (NMA). Method We searched MEDLINE, Embase, the Cochrane Library, CINAHL, and PsycINFO from inception until August 2022 to identify randomized clinical trials (RCTs) appraising treatments for depressive symptoms in cognitive impairment. Efficacy was apprised by Cornell Scale for Depression (CSDD), Hamilton Depression Rating Scale (HDRS) and Geriatric Depression Scale (GDS) for depression, Neuropsychiatric Inventory (NPI) and Cohen–Mansfeld Agitation Inventory (CMAI) for behavior, and Mini-Mental State Examination (MMSE) for cognition. Safety was evaluated by total adverse events (AEs), serious AEs, diarrhea, headache, and nausea. Results: 13043 participants from 107 RCTs were included involving 28 treatments and discontinuation of antidepressants. On CSDD, aerobic-exercise (MD -4.51, 95%CrI -8.60 to -0.37), aripiprazole (MD -1.85, 95%CrI -3.66 to -0.02), behavioral training (MD -1.14, 95%CrI -2.04 to -0.34), electrical current stimulation (MD -3.30, 95%CrI -5.94 to -0.73), massage (MD -12.67, 95%CrI -14.71 to -10.59)，music therapy (MD -2.63, 95%CrI -4.72 to -0.58) and reminiscence therapy(MD -2.34, 95%CrI -3.51 to -1.25) were superior to placebo significantly. On MMSE, cognitive stimulation therapy (MD 1.42, 95%CrI 0.49 to 2.39), electrical current stimulation (MD 4.08, 95%CrI 1.07 to 7.11) and reminiscence therapy (MD 1.31, 95%CrI 0.04 to 2.91) exhibited significance superior to placebo. Additionally, no treatments showed significantly higher risk than the placebo. Conclusion Our NMAs indicated that non-pharmacological interventions were more efficacious and safer than pharmacological treatments for reducing depressive symptoms as well as improving cognitive impairment. Especially, Electrical current stimulation, aerobic-exercise, and reminiscence therapy could be first recommended considering their beneficial performance on both depression and cognition. Hence, non-pharmacological treatments deserve more attention and extensive application, at least being considered as an alternative or assistance in clinical. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php? ID=CRD42021239621, identifier CRD42021239621.